2022
DOI: 10.51983/ajeat-2022.11.1.3310
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Drying Methods on Antioxidant Activity and Availability of Phytochemicals in Leaves of Costus speciosus, Coccinia grandis and Gymnema sylvestre

Abstract: Drying is an important method for preserving phytochemicals in plant materials though the stability is altered with the type of drying method. This study aimed at evaluating the effectiveness of different drying methods on antioxidant activity and phytochemical availability in leaf ethanolic extracts of Costus speciosus, Coccinia grandis, and Gymnema sylvestre. Plant leaves of the selected species were subjected to shade drying at room temperature (25 + 5℃), oven drying at 45 ℃ and freeze-drying methods. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…When exposed to elevated temperatures, certain heat-labile phytochemicals, including GA, can undergo degradation or chemical changes, resulting in reduced concentrations. This finding aligns with previous reports by Peries et al 66 and Sagrin and Chong 67 , which indicated that high drying temperatures can lead to the destruction of heat-labile phytochemicals in plant materials. Furthermore, the study suggested that drying temperatures above 60 °C could significantly mitigate the antioxidant content of the leaves 67 , 68 .…”
Section: Discussionsupporting
confidence: 93%
“…When exposed to elevated temperatures, certain heat-labile phytochemicals, including GA, can undergo degradation or chemical changes, resulting in reduced concentrations. This finding aligns with previous reports by Peries et al 66 and Sagrin and Chong 67 , which indicated that high drying temperatures can lead to the destruction of heat-labile phytochemicals in plant materials. Furthermore, the study suggested that drying temperatures above 60 °C could significantly mitigate the antioxidant content of the leaves 67 , 68 .…”
Section: Discussionsupporting
confidence: 93%